Analytical method for assessing potential dermal exposure to captan, using whole body dosimetry, in small vegetable production units in Argentina - Hughes, Enrique Alejandro (2006)
An analytical method has been developed that can be used to determine the potential dermal exposure (PDE) of workers to the pesticide captan in small-scale horticultural production units. The methodology is based on the whole body dosimetry technique, using a cotton coverall and cotton gloves as sampling media, with protective clothing worn beneath the cotton media to protect the operator. The quantitative determination of captan was done by gas chromatography-electron capture detector (GC-ECD), with the analytical method validated by measuring limits of detection and quantification, linear ranges, sample recovery and precision. Special emphasis is placed on factors that affected the stability of captan during chromatographic determination. The data generated for potential dermal exposure are presented separately for mixing/loading and application activities. These data are compared with values obtained with visible tracers using a similar field technique. Margin of safety (MOS) values are also calculated for the agricultural procedures studied.